High-strength lithium battery microporous diaphragm produced by wet process and preparation method thereof

By using modified coatings and specific process steps in the micro -hole diaphragm of lithium batteries, the problem of poor thermal stability of wet diaphragm has been solved, and the safety and performance of the battery significantly improved the safety and performance of the battery.

CN119381699AInactive Publication Date: 2025-01-28SHANXI HOUSHENG NEW MATERIAL TECH CO LTD

Patent Information

Application Number
CN202411516758.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-01-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing wet method produces high-strength lithium battery microporous membranes with poor thermal stability and are prone to shrink or melt under high temperature conditions, affecting the safety of the battery.

Method used

Adopt modified coatings, including flame retardants, adhesives, wetting agents, enhanced fillers and conductive agents, coated on the porous base membrane, and prepare height through process steps such as thermal phase separation method and two -way stretching Strength micropores.

Benefits of technology

Improve the flame retardant performance and thermal stability of lithium battery micropores, improve the safety performance and overall performance of the battery, and ensure the quality of the diaphragm.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005106920470000081
    Figure BDA0005106920470000081
Patent Text Reader

Abstract

The invention relates to a high-strength lithium battery microporous diaphragm produced by a wet method and a preparation method thereof, the diaphragm comprises a porous base membrane and a coating coated on one side or two sides of the porous base membrane, the material of the coating comprises a modified coating, and the modified coating comprises the following raw materials by weight: 18-38 parts of a flame retardant, 25-31 parts of an adhesive, 2-6 parts of a wetting agent, 3-8 parts of a reinforcing filler, 3-12 parts of a conductive agent, and 88-120 parts of N, N-dimethylformamide. The invention discloses a high-temperature-resistant adhesive which is prepared from the following components in parts by weight: 0.5-2.6 parts of N, N-dimethylformamide, 0.5-2.6 parts of acrylic acid, 0.1-1.2 parts of succinic anhydride When the modified coating is applied to the lithium battery diaphragm, the flame retardant property of the lithium battery diaphragm can be effectively improved, the safety performance of the lithium battery diaphragm is improved, and the quality of the lithium battery diaphragm is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium battery microporous diaphragms, and more specifically, to a wet-process high-strength lithium battery microporous diaphragm and a preparation method thereof. Background Art

[0002] The wet process for producing high-strength microporous lithium battery diaphragms is an advanced production process that mainly utilizes thermally induced phase separation (also known as phase separation or thermally induced phase separation). This process is performed by mixing liquid hydrocarbons or small molecules with polyolefin resins, heating and melting to form a uniform mixture, and then allowing solid-liquid or liquid-liquid phase separation to occur during the cooling process to produce a membrane. Next, the membrane is heated to a temperature close to the melting point and biaxially stretched to align the molecular chains, and finally a volatile solvent is used to extract the residual pore-forming agent, thereby preparing an interconnected nanoscale microporous membrane material.

[0003] Wet-process diaphragms have many advantages, such as higher porosity, more uniform pore size distribution, stronger tensile strength and puncture resistance, and thinner thickness. These characteristics make wet-process diaphragms very suitable for the production of high-performance, high-energy-density lithium batteries, especially in the field of power batteries. In addition, the wet process can further improve the thermal stability and mechanical strength of the diaphragm through coating technology, thereby improving the safety and overall performance of the battery.

[0004] In the existing technology, the thermal stability of high-strength lithium battery microporous diaphragms produced by the wet process is poor. Wet-process diaphragms usually use polyethylene (PE) as the substrate, which has a low melting point of only about 140°C. Therefore, it is easy to shrink or melt under high temperature conditions, which may affect the safety of the battery. Summary of the invention

[0005] The present invention provides a wet-process production of a high-strength lithium battery microporous diaphragm and a preparation method thereof. The modified coating is applied to the lithium battery diaphragm to effectively improve its flame retardant properties, thereby improving its safety performance while also ensuring its quality.

[0006] In the first aspect, the present invention provides a wet process for producing a high-strength lithium battery microporous diaphragm, comprising a porous base membrane and a coating coated on one side or both sides of the porous base membrane, wherein the material of the coating comprises a modified coating, and the modified coating comprises the following raw materials in parts by weight: 18 to 38 parts of a flame retardant, 25 to 31 parts of an adhesive, 2 to 6 parts of a wetting agent, 3 to 8 parts of a reinforcing filler, 3 to 12 parts of a conductive agent, 88 to 120 parts of N,N-dimethylformamide, 0.5 to 2.6 parts of acrylic acid, 0.1 to 1.2 parts of succinic anhydride, and 0.3 to 1.5 parts of triethylamine.

[0007] Preferably, it includes a porous base membrane and a coating coated on one side or both sides of the porous base membrane, the material of the coating includes a modified coating, and the modified coating includes the following raw materials in parts by weight: 25 to 35 parts of flame retardant, 28 to 31 parts of adhesive, 4 to 6 parts of wetting agent, 5 to 8 parts of reinforcing filler, 8 to 12 parts of conductive agent, 100 to 120 parts of N,N-dimethylformamide, 1.5 to 2.6 parts of acrylic acid, 0.8 to 1.2 parts of succinic anhydride, and 0.5 to 1.5 parts of triethylamine.

[0008] Preferably, it includes a porous base membrane and a coating coated on one side or both sides of the porous base membrane, the material of the coating includes a modified coating, and the modified coating includes the following raw materials in parts by weight: 36 parts of flame retardant, 29 parts of adhesive, 5 parts of wetting agent, 7 parts of reinforcing filler, 10 parts of conductive agent, 115 parts of N,N-dimethylformamide, 1.8 parts of acrylic acid, 0.5 parts of succinic anhydride, and 0.8 parts of triethylamine.

[0009] Preferably, the reinforcing filler comprises glass fiber, nano-boron nitride, nano-silicon dioxide, nano-zinc oxide and nano-titanium dioxide, and the mass ratio of the nano-boron nitride, nano-silicon dioxide, nano-zinc oxide and nano-titanium dioxide is (1-3): (1-2): (2-3): (5-1).

[0010] Preferably, the flame retardant is one or more of tetrabromobisphenol A, decabromodiphenylethane, phosphonates, phosphates, phosphites, organic phosphorus salts, phosphine oxides and phosphorus-nitrogen compounds.

[0011] Preferably, the adhesive is an epoxy compound, which includes the following raw materials in parts by weight: 15-36 parts of polyurethane, 6-24 parts of polydicyclopentadiene, 90-100 parts of methylhexahydrophthalic anhydride, 200-450 parts of copper hydroxide, 0.5-1.2 parts of N,N-dimethylbenzylamine, and 10-25 parts of special bisphenol A epoxy resin.

[0012] Preferably, the preparation method of the epoxy composite comprises the following steps: mixing polyurethane, polydicyclopentadiene, methylhexahydrophthalic anhydride, copper hydroxide, N,N-dimethylbenzylamine, and special bisphenol A epoxy resin, and stirring at a temperature of 100-150° C. to obtain the epoxy composite.

[0013] Preferably, the wetting agent includes one or more of EW-119, succinic acid, sodium polyacrylate, fatty acid polyoxyethylene ether, polysorbates, and polyoxyethylene fatty alcohol ethers.

[0014] Preferably, the particle size of the reinforcing filler is 60-130 nm.

[0015] In a second aspect, the present invention provides a method for preparing a high-strength lithium battery microporous membrane by a wet process, comprising the following steps:

[0016] (1) Mixing and melting: mixing a flame retardant, an adhesive, a wetting agent, a reinforcing filler, a conductive agent, N,N-dimethylformamide, acrylic acid, succinic anhydride, and triethylamine, and heating to a molten state to form a mixture;

[0017] (2) Casting and cooling: The porous base film is extruded through an extruder, and after flowing out of the die head, it is cooled and formed to form a thick sheet containing a pore-forming agent;

[0018] (3) Stretching: The mixture is coated on a thick sheet and then biaxially stretched to obtain a matrix;

[0019] (4) Extraction: After the substrate is stretched, the residual pore-forming agent is extracted using a solvent, dichloromethane, thereby forming an interconnected microporous structure in the substrate to obtain a film;

[0020] (5) Shaping and slitting: The film is dried and heat-set to obtain a high-strength lithium battery microporous diaphragm produced by a wet process.

[0021] Preferably, the pore size range of the high-strength lithium battery microporous membrane produced by the wet process is 0.01-0.05 μm.

[0022] In a third aspect, the present invention provides a lithium battery, comprising the high-strength lithium battery microporous diaphragm produced by the wet process as described in any one of claims 1 to 8.

[0023] In summary, the present invention has the following beneficial effects:

[0024] 1. In the lithium battery microporous diaphragm of the present invention, the flame retardant is added to the modified coating to improve the safety of the battery and prevent the battery from burning or exploding in the case of overheating or short circuit. The flame retardant can generate free radicals with flame retardant properties at high temperatures. These free radicals can capture combustible free radicals such as hydrogen and oxygen in the gas phase, prevent them from chain reaction, interrupt the combustion process, reduce the heat release value and self-heating rate of the battery, and improve the thermal stability of the electrolyte itself;

[0025] 2. In the lithium battery microporous diaphragm of the present invention, reinforcing fillers are added to the modified coating, and the flame retardant properties of the diaphragm are improved by doping glass fibers. The electrochemical properties of the lithium battery can be improved by adding nano-boron nitride, which can significantly improve the wettability, thermal stability and thermal conductivity of the diaphragm. The addition of nano-silicon dioxide helps to maintain the integrity and mechanical strength of the diaphragm. The addition of nano-titanium dioxide to the lithium battery microporous diaphragm not only improves the mechanical and electrochemical properties of the diaphragm, but also enhances its thermal stability and flame retardant properties, thereby improving the overall safety and service life of the battery;

[0026] 3. The high-strength lithium battery microporous diaphragm produced by the wet method of the present invention has good thermal stability. The micropore distribution uniformity of the wet method diaphragm is good and the porosity is high, which helps to improve the air permeability of the battery and the liquid absorption and retention capacity of the electrolyte, thereby reducing the internal resistance of the battery and improving the energy density and charge and discharge performance of the battery.

[0027] It should be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not intended to limit the scope of protection of the present invention. DETAILED DESCRIPTION

[0028] The present invention is further described in detail below in conjunction with the examples. It is particularly noted that if no specific conditions are specified in the following examples, the reactions are carried out according to conventional conditions or conditions recommended by the manufacturer. Unless otherwise specified, the raw materials used in the following examples can be obtained from common commercial sources.

[0029] Example

[0030] Example 1

[0031] A method for preparing a high-strength lithium battery microporous diaphragm by a wet process comprises the following steps:

[0032] (1) Mixing and melting: mixing a flame retardant, an adhesive, a wetting agent, a reinforcing filler, a conductive agent, N,N-dimethylformamide, acrylic acid, succinic anhydride, and triethylamine, and heating to a molten state to form a mixture;

[0033] (2) Casting and cooling: The porous base film is extruded through an extruder, and after flowing out of the die head, it is cooled and formed to form a thick sheet containing a pore-forming agent;

[0034] (3) Stretching: The mixture is coated on a thick sheet and then biaxially stretched to obtain a matrix;

[0035] (4) Extraction: After the substrate is stretched, the residual pore-forming agent is extracted using a solvent, dichloromethane, thereby forming an interconnected microporous structure in the substrate to obtain a film;

[0036] (5) Shaping and slitting: The film is dried and heat-set to obtain a high-strength lithium battery microporous diaphragm produced by a wet process.

[0037] The modified coating comprises the following raw materials in parts by weight: 36 parts of flame retardant, 29 parts of adhesive, 5 parts of wetting agent, 7 parts of reinforcing filler, 10 parts of conductive agent, 115 parts of N,N-dimethylformamide, 1.8 parts of acrylic acid, 0.5 parts of succinic anhydride and 0.8 parts of triethylamine.

[0038] The reinforcing fillers are nano boron nitride, nano silicon dioxide, nano zinc oxide and nano titanium dioxide in a mass ratio of 1:2:3:5;

[0039] The flame retardant is decabromodiphenylethane;

[0040] The adhesive is an epoxy compound, and the epoxy compound includes the following raw materials in parts by weight: 15 parts of polyurethane, 6 parts of polydicyclopentadiene, 90 parts of methyl hexahydrophthalic anhydride, 200 parts of copper hydroxide, 0.5 parts of N, N-dimethylbenzylamine, and 10 parts of special bisphenol A epoxy resin. The preparation method includes the following steps: polyurethane, polydicyclopentadiene, methyl hexahydrophthalic anhydride, copper hydroxide, N, N-dimethylbenzylamine, and special bisphenol A epoxy resin are mixed, and stirred at a temperature of 100° C. to obtain the epoxy compound.

[0041] The wetting agent includes EW-119; the particle size of the reinforcing filler is 80 nm.

[0042] Example 2

[0043] A method for preparing a high-strength lithium battery microporous diaphragm by a wet process comprises the following steps:

[0044] (1) Mixing and melting: mixing a flame retardant, an adhesive, a wetting agent, a reinforcing filler, a conductive agent, N,N-dimethylformamide, acrylic acid, succinic anhydride, and triethylamine, and heating to a molten state to form a mixture;

[0045] (2) Casting and cooling: The porous base film is extruded through an extruder, and after flowing out of the die head, it is cooled and formed to form a thick sheet containing a pore-forming agent;

[0046] (3) Stretching: The mixture is coated on a thick sheet and then biaxially stretched to obtain a matrix;

[0047] (4) Extraction: After the substrate is stretched, the residual pore-forming agent is extracted using a solvent, dichloromethane, thereby forming an interconnected microporous structure in the substrate to obtain a film;

[0048] (5) Shaping and slitting: The film is dried and heat-set to obtain a high-strength lithium battery microporous diaphragm produced by a wet process.

[0049] The modified coating comprises the following raw materials in parts by weight: 18 parts of flame retardant, 25 parts of adhesive, 2 parts of wetting agent, 3 parts of reinforcing filler, 3 parts of conductive agent, 88 parts of N,N-dimethylformamide, 0.5 parts of acrylic acid, 0.1-1.2 parts of succinic anhydride, and 0.3-1.5 parts of triethylamine.

[0050] The reinforcing filler is nano boron nitride, nano silicon dioxide, nano zinc oxide and nano titanium dioxide in a mass ratio of 3:1:2:3;

[0051] The flame retardant is decabromodiphenylethane;

[0052] The adhesive is an epoxy compound, which includes the following raw materials in parts by weight: 36 parts of polyurethane, 24 parts of polydicyclopentadiene, 100 parts of methyl hexahydrophthalic anhydride, 450 parts of copper hydroxide, 1.2 parts of N, N-dimethylbenzylamine, and 25 parts of special bisphenol A epoxy resin. The preparation method includes the following steps: mixing polyurethane, polydicyclopentadiene, methyl hexahydrophthalic anhydride, copper hydroxide, N, N-dimethylbenzylamine, and special bisphenol A epoxy resin, stirring at a temperature of 150° C. to obtain the epoxy compound.

[0053] The wetting agent includes EW-119; the particle size of the reinforcing filler is 80 nm.

[0054] Example 3

[0055] A method for preparing a high-strength lithium battery microporous diaphragm by a wet process comprises the following steps:

[0056] (1) Mixing and melting: mixing a flame retardant, an adhesive, a wetting agent, a reinforcing filler, a conductive agent, N,N-dimethylformamide, acrylic acid, succinic anhydride, and triethylamine, and heating to a molten state to form a mixture;

[0057] (2) Casting and cooling: The porous base film is extruded through an extruder, and after flowing out of the die head, it is cooled and formed to form a thick sheet containing a pore-forming agent;

[0058] (3) Stretching: The mixture is coated on a thick sheet and then biaxially stretched to obtain a matrix;

[0059] (4) Extraction: After the substrate is stretched, the residual pore-forming agent is extracted using a solvent, dichloromethane, thereby forming an interconnected microporous structure in the substrate to obtain a film;

[0060] (5) Shaping and slitting: The film is dried and heat-set to obtain a high-strength lithium battery microporous diaphragm produced by a wet process.

[0061] The modified coating comprises the following raw materials in parts by weight: 38 parts of flame retardant, 31 parts of adhesive, 6 parts of wetting agent, 8 parts of reinforcing filler, 12 parts of conductive agent, 120 parts of N,N-dimethylformamide, 2.6 parts of acrylic acid, 1.2 parts of succinic anhydride, and 1.5 parts of triethylamine.

[0062] The reinforcing filler is nano boron nitride, nano silicon dioxide, nano zinc oxide and nano titanium dioxide in a mass ratio of 1:1:2:5;

[0063] The flame retardant is decabromodiphenylethane;

[0064] The adhesive is an epoxy compound, and the epoxy compound includes the following raw materials in parts by weight: 25 parts of polyurethane, 12 parts of polydicyclopentadiene, 95 parts of methyl hexahydrophthalic anhydride, 380 parts of copper hydroxide, 0.8 parts of N, N-dimethylbenzylamine, and 12 parts of special bisphenol A epoxy resin. The preparation method includes the following steps: mixing polyurethane, polydicyclopentadiene, methyl hexahydrophthalic anhydride, copper hydroxide, N, N-dimethylbenzylamine, and special bisphenol A epoxy resin, stirring at a temperature of 100° C. to obtain the epoxy compound.

[0065] The wetting agent includes EW-119; the particle size of the reinforcing filler is 80 nm.

[0066] Comparative Example

[0067] Comparative Example 1

[0068] The difference between this comparative example and Example 1 is that no modified coating is added and other conditions remain unchanged.

[0069] Comparative Example 2

[0070] The difference between this comparative example and Example 1 is that the modified coating is replaced by polyvinylidene fluoride, and other conditions remain unchanged.

[0071] Comparative Example 3

[0072] The difference between this comparative example and Example 1 is that the modified coating does not include a flame retardant, and other conditions remain unchanged.

[0073] Comparative Example 4

[0074] The difference between this comparative example and Example 1 is that the modified coating does not include reinforcing filler, and other conditions remain unchanged.

[0075] Performance Testing

[0076] The tensile strength, liquid absorption rate, membrane rupture temperature and ionic conductivity of the high-strength lithium battery microporous diaphragms produced by the wet process in Examples 1-3 and Comparative Examples 1-4 were tested.

[0077] The specific detection methods are as follows:

[0078] (1) Tensile Strength The longitudinal and transverse tensile strength of the low-temperature resistant diaphragm at -20°C was tested using a CTM universal testing machine. The test was conducted in accordance with the requirements of GB / T1040.3-2006. The specimens were prepared by cutting method and the specimen type was Type 2 specimen. The specimen was in the shape of a strip with a length of 200 mm and a width of 25 mm. The distance between the fixtures was 100 mm. The test speed was 250 mm / min. Five strips were tested in each direction and the average value was calculated.

[0079] (2) Liquid absorption rate: After soaking the diaphragm in electrolyte (to reduce contamination, a mixed solution of EC / DMC / DEC with a volume ratio of 1:1:1 was used instead) for 10 minutes, the diaphragm was taken out, the excess liquid on the surface was wiped off with filter paper, and the liquid absorption rate was calculated.

[0080] (3) The membrane rupture temperature is measured by the resistance mutation method. The point where the resistance suddenly increases is the membrane rupture temperature.

[0081] (4) Ionic conductivity The bulk resistance was tested by using the electrochemical impedance spectroscopy (EIS) mode of a VMP3B-10 electrochemical workstation (Bio-Logic Science Instruments) in the assembly mode of steel sheet / diaphragm / steel sheet, with a perturbation voltage amplitude of 5 mV and a frequency of 10 mHz-1 MHz. The relationship between bulk resistance and ionic conductivity is that ionic conductivity is equal to the ratio of the membrane thickness to the product of the membrane resistance and the effective contact area.

[0082] Table 1 Performance test results

[0083]

[0084] It can be seen from the above performance test results that the tensile strength and conductivity of Examples 1-3 are relatively good, especially the comprehensive performance of Example 1 is the most outstanding. This is mainly because the role of adding flame retardants to the modified coating is mainly to improve the safety of the battery and prevent the battery from burning or exploding in the event of overheating or short circuit. The flame retardant can produce free radicals with flame retardant properties at high temperatures. These free radicals can capture combustible free radicals such as hydrogen and oxygen in the gas phase, prevent them from chain reactions, interrupt the combustion process, reduce the heat release value and self-heating rate of the battery, and at the same time improve the thermal stability of the electrolyte itself.

[0085] However, the comparative example did not adopt the necessary technical solution, resulting in that its corresponding performance tests were significantly worse than those of the embodiment. In comparative example 1, no modified coating was added, and it can be seen that the tensile strength decreased, proving that the modified coating has an important influence on the thermal stability and thermal conductivity of the lithium battery microporous membrane. The above experimental results further prove the importance of the technical solution defined in the present invention to its technical effect.

[0086] The above is only an exemplary embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A wet process for producing a high-strength lithium battery microporous membrane, characterized in that: The invention comprises a porous base film and a coating applied on one side or both sides of the porous base film, wherein the material of the coating comprises a modified coating, and the modified coating comprises the following raw materials in parts by weight: 18 to 38 parts of a flame retardant, 25 to 31 parts of an adhesive, 2 to 6 parts of a wetting agent, 3 to 8 parts of a reinforcing filler, 3 to 12 parts of a conductive agent, 88 to 120 parts of N,N-dimethylformamide, 0.5 to 2.6 parts of acrylic acid, 0.1 to 1.2 parts of succinic anhydride, and 0.3 to 1.5 parts of triethylamine.

2. The method of producing a high-strength lithium battery microporous diaphragm by wet method according to claim 1, characterized in that: The reinforcing filler comprises glass fiber, nano boron nitride, nano silicon dioxide, nano zinc oxide and nano titanium dioxide, and the mass ratio of the nano boron nitride, nano silicon dioxide, nano zinc oxide and nano titanium dioxide is (1-3): (1-2): (2-3): (5-1).

3. The wet method for producing a high-strength lithium battery microporous diaphragm according to claim 1, characterized in that: The flame retardant is one or more of tetrabromobisphenol A, decabromodiphenylethane, phosphonate, phosphate, phosphite, organic phosphorus salt, phosphine oxide and phosphorus-nitrogen compound.

4. The method of producing a high-strength lithium battery microporous diaphragm by wet method according to claim 1, characterized in that: The adhesive is an epoxy compound, which comprises the following raw materials in parts by weight: 15-36 parts of polyurethane, 6-24 parts of polydicyclopentadiene, 90-100 parts of methylhexahydrophthalic anhydride, 200-450 parts of copper hydroxide, 0.5-1.2 parts of N, N-dimethylbenzylamine, and 10-25 parts of special bisphenol A epoxy resin.

5. The wet method for producing a high-strength lithium battery microporous diaphragm according to claim 1, characterized in that: The preparation method of the epoxy compound comprises the following steps: mixing polyurethane, polydicyclopentadiene, methylhexahydrophthalic anhydride, copper hydroxide, N,N-dimethylbenzylamine and special bisphenol A epoxy resin, and stirring at a temperature of 100-150 DEG C to prepare the epoxy compound.

6. The wet method for producing a high-strength lithium battery microporous diaphragm according to claim 1, characterized in that: The wetting agent includes one or more of EW-119, succinic acid, sodium polyacrylate, fatty acid polyoxyethylene ether, polysorbates, and polyoxyethylene fatty alcohol ethers.

7. The wet method for producing a high-strength lithium battery microporous diaphragm according to claim 1, characterized in that: The particle size of the reinforcing filler is 60-130 nm.

8. The method for preparing a high-strength lithium battery microporous diaphragm by wet production according to any one of claims 1 to 7, characterized in that: The following steps are involved: (1) Mixing and melting: mixing a flame retardant, an adhesive, a wetting agent, a reinforcing filler, a conductive agent, N,N-dimethylformamide, acrylic acid, succinic anhydride, and triethylamine, and heating to a molten state to form a mixture; (2) Casting and cooling: The porous base film is extruded through an extruder, and after flowing out of the die head, it is cooled and formed to form a thick sheet containing a pore-forming agent; (3) Stretching: The mixture is coated on a thick sheet and then biaxially stretched to obtain a matrix; (4) Extraction: After the substrate is stretched, the residual pore-forming agent is extracted using a solvent, dichloromethane, thereby forming an interconnected microporous structure in the substrate to obtain a film; (5) Shaping and slitting: The film is dried and heat-set to obtain a high-strength lithium battery microporous diaphragm produced by a wet process.

9. The method for preparing a high-strength lithium battery microporous diaphragm by wet production according to claim 8, characterized in that: The pore size range of the wet-process produced high-strength lithium battery microporous membrane is 0.01-0.05μm.

10. A lithium battery, characterized in that: It includes the wet method for producing a high-strength lithium battery microporous diaphragm as described in any one of claims 1 to 8.

Citation Information

Patent Citations

  • Polyolefin multilayer microporous film, method for producing same, and cell separator

    CN107405902A

  • Modified coating for lithium battery diaphragm and lithium battery diaphragm

    CN118336162A

  • Flame-retardant composite diaphragm, preparation method thereof and lithium ion battery

    CN118783033A

Cited By

  • Production equipment for high-bearing structural battery diaphragm

    CN120413981A